Mediating social entrepreneurship in South Africa and India: exploring the entanglements of neoliberal logics and social missions - Chopra, Vrinda (Department of Environmental and Geographical Science, 2022)
Entrepreneurial approaches advocated as pathways for addressing development goals of unemployment and inequality have been heavily criticised. Critical development scholarship argues that entrepreneurship for development contributes to the deepening hegemony of neoliberal logics (market and finance). I argue that there is scope to problematise the claims of the power and centrality of neoliberal economic logics by viewing these logics in relation with social ones such as trust, morality, reciprocity, exchange, justice (among others). Towards these ends, I focus on social entrepreneurship given the assertions of it being a hybrid field combining the logics of the private sector (markets, finance) with those of the state and civil society (socio-economic change) to deepen efficiency in addressing development goals. Specifically, I focus on a qualitative study based on ethnographic principles of thick description of the meso in-between scales (that is between macro-perspectives on social entrepreneurship and micro-realities of social enterprise practice) in postcolonial emerging economies of South Africa and India. The meso-scale is made up of intermediary organisations providing support services, networking spaces and knowledge to start and grow enterprises geared towards development goals. An analysis of these intermediaries enabled a view into three interlinked issues that I demonstrate in the thesis. One, applying and deploying entrepreneurial approaches like social entrepreneurship produces significant tensions as practitioners attempt to align with economic logics of market and finance, while dealing with complex development challenges. Two, the daily work of intermediaries is fraught with confusions as they attempt to balance out economic and social logics, often resulting in visible leanings towards measurable categories to manage the arising difficulties. Finally, as intermediaries navigate entangled economic and social logics, the ambivalent nature of their work emerges. It is precisely this inchoate and ambivalent nature of practice that problematises the centrality of neoliberal economic logics within development, leading to considerations that power between economic and social logics is negotiated relationally, in an on-going, uncertain manner.